Adsorptive recycle of phosphate by MgO-biochar from wastewater: Adsorbent fabrication, adsorption site energy analysis and long-term column experiments. (February 2023) - Chen, Dong; Yin, Yue; Xu, Yanming; Liu, Changqing
Abstract: Magnesium doped spent coffee grounds (Mg-SCG) biochar was fabricated in this research and its adsorption performance was investigated thoroughly in batch and column studies. The effects of time, pH, organic matter, co-existing anions, and water matrices on phosphate removal were explored. The 500 °C pyrolysis temperature (Mg-SCG-500) was proved to be the optimal condition for phosphate adsorption and achieved 111.20 mg/g theoretical maximum adsorption capacity. The adsorption site energy analysis revealed that 500 °C pyrolysis temperature also provided more sites with suitable adsorption energy for phosphate adsorption. The used Mg-SCG-500 could be efficiently desorbed and regenerated using 1 M NaOH and recalcination. Meanwhile, Mg-SCG showed great stability under realistic conditions. In long-term column experiments, 20 cycles of adsorption were conducted with different contact times, total treated volume, and water matrices. The results proved that the Mg-SCG based column could efficiently remove the phosphate from aqueous solutions. This work would extend the potential application of Mg-SCG based column, acting as a promising solution for phosphate removal and recycle from real wastewater. Highlights: Synthesis of Mg-doped spent coffee grounds (Mg-SCG) based biochar was optimized. Mg-SCG exhibited 91.14 mg/g capacity with low equilibrium concentration. Long-term column performance of MgO-biochar was thoroughly investigated. Successful recycle of phosphate was achieved by Mg-SCG based column.